Development Prospects Labor Income of the Population of the Republic of Kazakhstan: Economic Efficiency and Priorities of Regulation - Omarova, A.; Kurmangaliyeva, L.; Yerzhanova, S.; Kuttybaeva, N.; Abdikarimova, A.; Jazykbayeva, B. (Montenegrin Journal of Economics, 2023)
This study examines the main factors influencing the formation of labor re-sources, which are interconnected with demographic changes that affect labor resources and, as a result, economic growth. This, of course, depends on several complex factors, including the nature and pace of demographic change, the functioning of labor and capital markets, macroeconomic and trade policy management, and the management and accumulation of hu-man capital. However, the labor change model can take into account signif-icant differences in past economic performance between regions and helps to identify more and less promising conditions for future economic growth. Understanding the challenges and implications of a country's changing pop-ulation size and age structure, population replacement trends and pro-spects, and the links between demographic processes and labor and in-come generation will help the government develop policies that build on the economic potential inherent in the changes that are currently taking place.
Keywords: Labor resources; labor income; demographic situation; economic growth; demographic policy; socio-economic policy.